Enhanced Photon Emission of Chemiluminescent Luminophore for Ultra-Fast and Semi-Automatic Immunoassay toward Single Molecule Detection - Ren, Xiaoxuan; Gao, Xuwen; Zou, Guizheng (Analytical chemistry (Washington), 2023)
Optical single molecule detection is normally achieved via amplifying the total emission of photons of luminophores and is strongly anticipated to extend the commercialized application of chemiluminescence (CL). To overcome the limited CL photons of molecule luminophores, herein, a nanocrystal (NC) luminophore self-amplified strategy is proposed to repetitively excite CL luminophores for amplifying the total CL photons per luminophore, which can be exploited to perform CL immunoassays (CLIAs) toward single molecule detection via employing KMnO4 as the CL triggering agent and the dual-stabilizer-capped CdTe NCs as the CL luminophore. KMnO4 can oxidize the S element from each stabilizer of mercaptopropionic acid (MPA) and release enough energy to excite the CdTe core for flash CL. The substantial MPA around each CdTe core enables every CdTe luminophore to be repetitively excited and give off amplified total CL photons in a self-enhanced way. The CL of CdTe NCs/KMnO4 can release all photons rapidly, and the collection of all these photons can be utilized to determine the model analyte of thyroid-stimulating hormone antigen (TSH) with a limit of detection of 5 ag/mL (S/N = 3), which is corresponding to about 2–4 TSH molecules in a 20 μL sample. The whole immunologic operating process can be terminated within 6 min. This strategy of repetitively breaking the CL reaction involving chemical bonds within one luminophore is promising for semi-automatic as well as fully automatic single molecule detection and extends the commercialized application of CL immunodiagnosis.